The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1109/access.2022.3233767
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Power Quality Disturbance Using Segmented and Modified S-Transform and DCNN-MSVM Hybrid Model

Abstract: In this paper, a novel approach to classify the signals of power quality (PQ) disturbance is proposed based on segmented and modified S-transform (SMST), deep convolutional neural network (DCNN), and multiclass support vector machine (MSVM). The idea of frequency segmentation with different adjustable parameters was used in the Gaussian window function. The accurate time-frequency localization and efficient feature extraction of different PQ disturbances then could be achieved. Firstly, the SMST was used to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Liu et al [87] proposed an innovative approach to classifying power quality disturbances in the system using a deep convolutional neural network, multi-class support vector machine (MSVM) and segmented and modified S-transform (SMST). The test results showed that this method is characterised by high efficiency.…”
Section: Power Qualitymentioning
confidence: 99%
“…Liu et al [87] proposed an innovative approach to classifying power quality disturbances in the system using a deep convolutional neural network, multi-class support vector machine (MSVM) and segmented and modified S-transform (SMST). The test results showed that this method is characterised by high efficiency.…”
Section: Power Qualitymentioning
confidence: 99%
“…The model was evaluated on synthetic and experimental data collected from process-adaptive VMD data. The overall The algorithm of a CNN for PQ detection and analysis comprises five major stages [11]. Stage-1 convolution stage: the input image is convolved with multiple filters to extract features.…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%
“…In this case, the Long Short Term Memory (LSTM) network is used to categorize the signals based on their properties as a succession of disturbances. In [16], based on segmented and modified Stransform, deep convolutional neural network, and multiclass support vector machine, a novel method for classifying PQD is proposed.…”
Section: Literature Reviewmentioning
confidence: 99%